2020
DOI: 10.3892/etm.2020.9089
|View full text |Cite
|
Sign up to set email alerts
|

Exendin‑4 inhibits atrial arrhythmogenesis in a model of myocardial infarction‑induced heart failure via the GLP‑1 receptor signaling pathway

Abstract: Glucagon-like peptide-1 receptor (GLP-1 receptor) agonists are considered to exert cardioprotective effects in models of acute and chronic heart disease. The present study aimed to investigate the role of exendin-4 (a GLP-1 receptor agonist) in atrial arrhythmogenesis in a model of myocardial infarction (MI)-induced heart failure and to elucidate the mechanisms underlying its effects. For this purpose, male Sprague-Dawley rats underwent sham surgery or left anterior descending artery ligation prior to being tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Indeed, in a canine AF model, liraglutide was found to suppress atrial electrophysiological changes such as AF inducibility and conduction velocity decrease [ 32 ]. Consistently, in a rat model of MI‑induced heart failure, exendin-4 decreased susceptibility to atrial arrhythmogenesis, improved conduction properties, and attenuated atrial fibrosis [ 33 ]. GLP-1RAs might also protect diabetic hearts from AF development through modulating calcium homeostasis.…”
Section: Extracerebral Effects Of Glucagon-like Peptide-1 Receptor Ag...mentioning
confidence: 89%
“…Indeed, in a canine AF model, liraglutide was found to suppress atrial electrophysiological changes such as AF inducibility and conduction velocity decrease [ 32 ]. Consistently, in a rat model of MI‑induced heart failure, exendin-4 decreased susceptibility to atrial arrhythmogenesis, improved conduction properties, and attenuated atrial fibrosis [ 33 ]. GLP-1RAs might also protect diabetic hearts from AF development through modulating calcium homeostasis.…”
Section: Extracerebral Effects Of Glucagon-like Peptide-1 Receptor Ag...mentioning
confidence: 89%
“…The effects on AF/AFL risk reductions of GLP-1RAs have hitherto received scant attention. Chen et al 55 reported that GLP-1RAs decreased susceptibility to atrial arrhythmogenesis by improving conduction properties and exerting antifibrotic effects via the GLP-1 receptor signaling pathway. A previous study indicated that albiglutide may increase the risk of tachyarrhythmia and AF.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical study also indicated Liraglutide reduced LV diastolic filling and LV filling pressure and unloaded the LV ( 28 ). The other mechanisms may involve inhibition of the PI3K/AKT signaling pathway and attenuation of atrial fibrosis yet ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous preclinical studies have been conducted to validate the effects of GLP-1RAs on cardiac arrhythmias under the disease state of MI. Chen et al found that treatment with exendin-4 reduced atrial fibrosis and inhibited atrial arrhythmias in the rat model of MI ( 14 ). Another animal study demonstrated that exendin-4 administered 1 h before ligation of the left anterior descending coronary artery in rats significantly prevented the development of ventricular arrhythmias after ischemia, such as reducing the incidence of ventricular fibrillation (VF) and the duration and number of ventricular tachycardia (VT) and VF episodes ( 15 ).…”
Section: Introductionmentioning
confidence: 99%